-6+5x=2+3x-2x

Simple and best practice solution for -6+5x=2+3x-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+5x=2+3x-2x equation:


Simplifying
-6 + 5x = 2 + 3x + -2x

Combine like terms: 3x + -2x = 1x
-6 + 5x = 2 + 1x

Solving
-6 + 5x = 2 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-6 + 5x + -1x = 2 + 1x + -1x

Combine like terms: 5x + -1x = 4x
-6 + 4x = 2 + 1x + -1x

Combine like terms: 1x + -1x = 0
-6 + 4x = 2 + 0
-6 + 4x = 2

Add '6' to each side of the equation.
-6 + 6 + 4x = 2 + 6

Combine like terms: -6 + 6 = 0
0 + 4x = 2 + 6
4x = 2 + 6

Combine like terms: 2 + 6 = 8
4x = 8

Divide each side by '4'.
x = 2

Simplifying
x = 2

See similar equations:

| 14v-16v=40 | | (1/5)x=-14 | | X/x+2=5/4 | | 77=4x+7x | | 4t^2+28t=0 | | 81-y^2=0 | | 16x-6=36x+9 | | x-(1/10)=(1/9) | | -2x-8=-6x-52 | | -7(x+2)-12=25+5 | | 2x/x^2-25=10/x^2-25-3/x+5 | | 16=8w-4/2 | | -10+5=x+8 | | 36b^2-49t^2= | | S=uz | | 7x^2-10x+10=0 | | 17-5+x=5+8-1 | | 96-y=3y | | 12a^2-11a-15= | | X-9/4-3=x-7/3 | | f(x)=5x^2+4x | | x-7/2(-4)=x-1/3 | | 12x-19x=74-18 | | 5+3q=7+2q | | 12x-35=-35+12x | | X-7/2-4=x-1/3 | | B=6+2(y-4) | | 6-(x+2)=5(3x-4) | | 11x/20-9=x/5+12 | | 6x-2y+12w+7y-3w+5x= | | 5y+4y+6x+5x-13y+4w= | | 5n/2-3/7=64/14 |

Equations solver categories